Primary Beam Air Kerma Dependence on Distance from Cargo and People Scanners. Issue 6 (June 2016) - Strom, Daniel J.; Cerra, Frank
Abstract : Abstract: The distance dependence of air kerma or dose rate of the primary radiation beam is not obvious for security scanners of cargo and people in which there is relative motion between a collimated source and the person or object being imaged. To study this problem, one fixed line source and three moving-source scan-geometry cases are considered, each characterized by radiation emanating perpendicular to an axis. The cases are 1) a stationary line source of radioactive material, e.g., contaminated solution in a pipe; 2) a moving, uncollimated point source of radiation that is shuttered or off when it is stationary; 3) a moving, collimated point source of radiation that is shuttered or off when it is stationary; and 4) a translating, narrow "pencil" beam emanating in a flying-spot, raster pattern. Each case is considered for short and long distances compared to the line source length or path traversed by a moving source. The short distance model pertains mostly to dose to objects being scanned and personnel associated with the screening operation. The long distance model pertains mostly to potential dose to bystanders. For radionuclide sources, the number of nuclear transitions that occur a) per unit length of a line source or b) during the traversal of a point source is a unifying concept. The "universal source strength" of air kerma rate at 1 m from the source can be used to describe x-ray machine or radionuclide sources. For many cargo and people scanners with highly collimated fan or pencil beams, dose varies as the inverse of the distance from the source in the near field and with the inverse square of the distance beyond a critical radius. Ignoring the inverse square dependence and using inverse distance dependence is conservative in the sense of tending to overestimate dose.